Konsep Pendidikan Islam Menurut Surat Al-Kahfi dalam Kisah Nabi Musa dan Khidir - stainu, ghazali; Mubarok, Moh Yazid (STAINU Purworejo, 2018)
The Story Moses and Al-Khidrin the qur’an can be said to have anassociation with education if in the educational process contains some basic elements,namely; (1) materials (2) the purpose of education (3) learners (4) educators (5) educational methods (6) educational situation (7) educational tools.The concept of Islamic education in Surat al Kahf has separate characteristics and privileges.The concept of Islamic education according to the letter al kahf in the story of the prophet Moses and khidr is an effort to transform values and science that combines the external and internal knowledge of educators as the center of role models to learners with the aim to achieve human perfection that leads to the self approach to God in reaching the happiness of the world and the hereafter. Kata Kunci: